Health Care Providers Perception and Practice of HIV Disclosure to Sero-Positive Children and Adolescents in a Tertiary Health Facility in Abuja, Nigeria - AA Okechukwu; V Kwaghe; A U Dike (Journal of Clinical Research In HIV AIDS And Prevention, 2018)
Background: Ideally, disclosure of HIV status to infected children and adolescents should involve both health care workers and parents/caregivers. Most studies on disclosure in children have focus mainly on parents/caregivers with little information on health care workers. We conduct this study to evaluate the practice, perception of the healthcare workers in our health facility on disclosure to infected children and adolescents. It is envisaged that such information will help in the design of better strategies on disclosure in our environment. Methods: A cross sectional hospital based study was conducted among health care workers at the special treatment clinic, and heart to heart unit of the University of Abuja Teaching Hospital, Gwagwalada from January to March 2017 for the above objective. A structured questionnaire was used to collect information on disclosure among the healthcare workers, which include among others: their bio-data, knowledge, perception, and practice on disclosure in the two service areas of the hospital. Results: Of the 80 health care workers interviewed, 60(75.0%) were females, 11(13.8%) were doctors, 9(11.3%) nurses, 17(21.3%) monitoring/evaluation/record clerks, and 16(20.0%) were either voluntary counseling and testing counselors or adherence counselors. Their mean age and duration in service in the two areas were 39.70±7.10 and 7.93±4.99 years respectively. Over half 48(60.0%) of the health care workers were unaware of the hospital having guideline on disclosure, 64(80.0%) have not been trained, and 68(85.0%) does not know any key information on disclosure. While all 80(100%) felt that disclosure was a good practice for better adherence, only 16(20.0%) had actually disclosed, with 6(37.5%) not seeking any formal permission from parent/caregivers before disclosing. Ages 8-16 years was recommended by 60(75%) as the appropriate age to disclose, however 28(35.0%) recommended age 14-16 years. Over half of the respondents 58(72.5%) admitted that disclosure should be a shared responsibility between themselves and the caregivers, most however perceive their role as only preparing the parents/caregivers for disclosure, and providing ongoing counseling to both the parents/caregivers and the children and adolescents. Lack of training on disclosure, and none availability of guideline in the health institution were major setback on the ability of the healthcare providers to fully participate in disclosure process. Conclusion: While healthcare providers support the idea of disclosing at mid and late adolescent, their perceived role was that of support and provision of ongoing counseling. Lack of training and none availability of disclosure guideline affects their perceived role. There is need to train and retrain healthcare workers on disclosure guideline, and making such guideline available in the health facilities.
Keywords: Disclosure